Microbial Diversity and Ecosystem Function - Allsopp, D; Ed. Colwell, Rita R; Ed. Hawksworth, D. L; Ed (CAB International, 1995)
In this volume, more than 30 contributors cover a wide range of topics that include the extent of microbial diversity, the impact of micro-organisms on global ecology and nutrient cycling.